the reckless oath we made - Greenwood, Bryn (New York : Putnam's Sons, 2020)
Their journey will break them - or save them. A moving and complicated love story for our time, The Reckless Oath We Made redefines what it means to be heroic. Zee has never admitted to needing anybody. But she needs Gentry. Her tough exterior shelters a heart that's loyal to the point of self-destruction, while autistic Gentry wears his heart on his sleeve, including his desire to protect Zee at all costs. When an abduction tears Zee's family apart, she turns to Gentry - and sets in motion a journey and a love that will change their lives forever
Keywords: Man-woman relationships -- Fiction; Kidnapping -- Fiction; Domestic fiction